For home and country : World War I propaganda on the home front - Kingsbury, Celia Malone (Studies in war, society, and the military., 2010)
World War I prompted the first massive organized propaganda campaign of the twentieth century. Posters, pamphlets, and other media spread fear about the "Hun", who was often depicted threatening American families in their homes, while additional campaigns encouraged Americans and their allies to support the war effort. With most men actively involved in warfare, women and children became a special focus and a tool of social manipulation during the war. This work examines the propaganda that targeted noncombatants on the home front in the United States and Europe during World War I. Cookbooks, popular magazines, romance novels, and government food agencies targeted women in their homes, especially their kitchens, pressuring them to change their domestic habits. Children were also taught to fear the enemy and support the war through propaganda in the form of toys, games, and books. And when women and children were not the recipients of propaganda, they were often used in propaganda to target men. By examining a diverse collection of literary texts, songs, posters, and toys, the author reveals how these pervasive materials were used to fight the war's cultural battle.